A study on out-of-field leakage of an accelerator-based neutron beam for boron neutron capture therapy - You, Zhen-Fan; Huang, Chun-Kai; Liu, Yen-Wan Hsueh (Frontiers in Oncology, 2024)
More and more accelerator based boron neutron capture therapy (AB-BNCT) facilities are under the construction or commissioning stage, and the neutron beam characteristics measurements at each facility will start soon. In addition to the in-field neutron beam properties, the leakage of neutron beam is also important, which is related to side effects of the patient. In the Virtual Technical Meeting on Advances in Boron Neutron Capture Therapy held by IAEA in July, 2020, the issue of the out-of-field leakage in boron neutron capture therapy was addressed. Heron Neutron Medical Corporation has been working on the beam design for China Medical University Hsinchu Hospital AB-BNCT research center. To evaluate the out-of-field leakage, an ORNL MIRD mathematical phantom is used to calculate the whole-body dose. For estimated irradiation time for 80 % of tumor dose reaches 20 Gy-w, the RBE weighted dose of abdomen region is less than 40 mGy-w, The whole-body dose is 104 mSv. The beam profile is also calculated. The neutron ambient dose equivalent at 15 cm from the field edge is 11 mSv/Gy-w and drops to 5 mSv/Gy-w at 26 cm from the field edge. The gamma ray ambient dose equivalent is less than 1 mSv/Gy-w starting from 10 cm from the field edge. Although the neutron out-of-field leakage of the beam design is higher than the initially proposed guideline by IAEA in 2020, the whole-body dose, however, is reasonably low. Both the whole-body dose evaluation and the beam profile analysis are useful in the beam design consideration. The whole-body dose calculation together with the beam profile analysis can also be helpful in reaching an acceptable recommendation for the out-of-field leakage for BNCT neutron beam, a job wish to be accomplished in the near future as proposed in the 2023 IAEA’s report on Advances in Boron Neutron Capture Therapy.